Pengembangan Lembar Kerja Peserta Didik Berbasis Realistic Mathematics Education dengan Konteks Kemaritiman untuk Peserta Didik SMA Kelas XI - Maimunah; Nur Izzati; Alona Dwinata (Jurnal Gantang, 2019)
The lack of use of teaching materials that are able to help learners to understand mathematics learning in schools causes the achievement of students' mathematical skills are still in the low category. The aims of this study is to develop a valid, practical and effective LKPD based on RME approach by using maritime context. This research is a type of Research and Development (R&D) research with a limited ADDIE development model that are Analysis, Design, and Development (ADD) stage. Data in the study were collected by the test and questionnaire methods. The research instruments used were expert validation sheets, student questionnaire response sheets, and test sheets. Data was analyzed with descriptive analysis to measure the validity of LKPD, Rasch modeling to measure the practicality of LKPD, and compare individual and classical minimum completeness criteria from students' post-test results to measure the effectiveness of LKPD. The results showed that LKPD based on RME fulfilled valid criteria with the dominance of the assessment in the good category, practical criteria with the dominant response of students in the practical category, and effective with a percentage of completeness of 87%.